Management of civilian penetrating rectal injuries in an urban trauma centre - Govender, Terron (Division of General Surgery, 2025)
Background: Rectal injuries are associated with significant morbidity. Primary repair of extraperitoneal rectal injuries, presacral drainage (PSD) and distal rectal washout (DRW) have become historical adjuncts. Aim: A retrospective review was performed to determine the outcome of rectal injuries in an urban trauma centre with a high incidence of penetrating trauma where a simple surgical management approach to these injuries is practiced. Methods: The records of all patients with a full-thickness penetrating rectal injury admitted to the Trauma Centre at Groote Schuur Hospital over a 10-year period (January 2010 – December 2019) were reviewed. Basic demographics, injury mechanism and perioperative management, anatomical site of the rectal injury, associated intra-abdominal injuries and their management were recorded. Infectious complications and mortality were noted. Intraperitoneal rectal injuries were primarily repaired, with or without faecal diversion. Extraperitoneal rectal injuries were generally left untouched, and a diverting loop colostomy done. Intraperitoneal bladder injuries were primarily repaired and extraperitoneal bladder injuries were repaired from within the bladder. Pelvic and spinal fractures were copiously lavaged. Presacral drainage and DRW were not performed. Results: One-hundred and four (101: gunshot; 3: stab) patients with 134 rectal injuries [intraperitoneal (10), extraperitoneal (64), combined (30)] were identified. Transpelvic trajectory was identified in 75 (72.12%) patients. Associated genitourinary tract injuries occurred in 42 (40.38%) patients and included 27 (25.96%) bladder injuries [intraperitoneal (9), extraperitoneal (4), combined (14)] and seven (6.73%) distal ureter injuries. Fifty patients 6 (48.08%) had associated bony injuries: sacrum (22), iliac (9), pubic rami (5), coccyx (1), acetabulum (3), femur (6), vertebral fractures (3) and pelvic joints (5). Eight (7.69%) patients had an associated vascular injury [iliac veins (4), iliac arteries (4)]. Two extraperitoneal rectal injuries were repaired. Diverting loop colostomies (91) and three Hartmann's type procedures were done for the remaining untouched extraperitoneal rectal injuries. None had PSD or DRW. Nine (6.7%) fistulae were recorded: three rectocutaneous, three rectovesical, one small bowel cutaneous, one vesicocutaneous and one entero-enteric. There were 27 infectious complications: surgical site infection (13), iliac blade and sacral osteitis (2), other soft tissue infections (12). Conclusion: Extraperitoneal rectal injuries due to low-velocity trauma can be safely managed by faecal diversion, without repair, DRW and PSD with minimal morbidity.